Women's Satisfaction on Maternal Healthcare Services in Public Health Facilities: A Case of Meta Maternity Hospital (Tanzania Medical Journal, 2025)
BackgroundSatisfaction with healthcare services serves as a key measure of quality in healthcare systems. Although the Ministry of Health in Tanzania has introduced attentive and respectful health service, the satisfaction levels among pregnant women with delivery services at public hospitals remain inadequately addressed.ObjectiveTo analyze women's satisfaction with maternal healthcare services at Meta Maternity Hospital in Tanzania and identifies factors influencing their satisfaction.MethodologyA hospital-based cross-sectional study design was employed, targeting pregnant women attending Meta Maternity Hospital in the Mbeya region from September 2022 to March 2023. Data were collected through a pre-tested structured questionnaire to gather information about socio-demographic characteristics and their level of satisfaction with the cleanliness of the health facility. Bivariate and multivariate analyses were conducted using binary logistic regression to identify factors associated with a high level of satisfaction.ResultsAll participants were satisfied with the healthcare facility's cleanliness, with 66.9% being delighted and others somewhat satisfied. Satisfaction varied significantly with the number of maternal visits, with those having 8-12 visits reporting the highest levels of satisfaction. Satisfaction with provider behavior was higher for the language used by healthcare providers (47.7%) compared to other behaviors. Women with 4–8 maternal visits were 0.4 times (95% CI = 0.203–0.692) and those with 8–12 visits were 0.3 times (95% CI = 0.194–0.586) as likely to be very satisfied with the cleanliness of the healthcare facility compared to those with 1–4 visits.Conclusion and recommendationPregnant women at Meta Maternity Hospital in Tanzania are generally satisfied with the cleanliness of healthcare facilities and provider behavior, especially the language used. However, more maternal visits are associated with lower satisfaction with cleanliness, suggesting a complex relationship where increased visits do not necessarily lead to higher satisfaction. While maintaining the current standards of cleanliness and provider behavior, Meta Maternity Hospital should investigate and address specific factors contributing to lower satisfaction with cleanliness among women with frequent maternal visits to improve overall satisfaction.